2009
DOI: 10.1038/modpathol.2009.93
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal copy number changes supporting the classification of lentiginous junctional melanoma of the elderly as a subtype of melanoma

Abstract: Recently the term lentiginous melanoma of the elderly has been suggested for a pattern of melanocytic neoplasia characterized by frequent occurrence in elderly patients, broad lentiginous growth pattern, with poorly cohesive nesting, suprabasilar extension of melanocytes and moderate cytological atypia. However, there are limited reported cases with follow-up information to confirm the malignant nature of these neoplasms. Using fluorescence in situ hybridization (FISH) targeting chromosomal loci that are frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
24
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 8 publications
6
24
0
Order By: Relevance
“…However, the impact of thickness on FISH results was not shown by the study by Gerami et al 10 A recent study proved the feasibility of this FISH test for in situ (very thin) melanocytic lesions in the so-called lentiginous junctional melanoma of the elderly. 14 In this study, three out of 19 in situ melanomas were FISH negative. The main difficulty concerning melanocytic lesions is to define the gold standard for malignancy.…”
Section: Discussionmentioning
confidence: 60%
“…However, the impact of thickness on FISH results was not shown by the study by Gerami et al 10 A recent study proved the feasibility of this FISH test for in situ (very thin) melanocytic lesions in the so-called lentiginous junctional melanoma of the elderly. 14 In this study, three out of 19 in situ melanomas were FISH negative. The main difficulty concerning melanocytic lesions is to define the gold standard for malignancy.…”
Section: Discussionmentioning
confidence: 60%
“…1 Although histological evaluation is a reliable means of accurately classifying melanocytic tumors as benign (nevi) or malignant (melanoma), this distinction can be difficult in a minority of cases. Based on the fact that melanomas are characterized by chromosomal aberrations, molecular genetic tests such as comparative genomic hybridization (CGH) [2][3][4] and fluorescence in situ hybridization [5][6][7][8] have been shown to be useful ancillary techniques, which assist accurate classification of melanocytic tumors. Multiple chromosomal gains and losses are identified with CGH in the majority (495%) of melanomas, whereas melanocytic nevi typically lack chromosomal aberrations.…”
mentioning
confidence: 99%
“…Our results seem contradictory to recent studies reporting high sensitivity and specificity of the four FISH probes. 9,10,12 However, these studies did not include histologically ambiguous lesions, and the results of the FISH analysis had been compared with the primary histological diagnosis but not to the clinical long-term follow up, considered the diagnostic gold standard. That said, the development of metastases during the long-term follow up is not conclusive of the malignant potential of the primary melanocytic lesion, and may instead arise from a separate unknown primary elsewhere in the body.…”
Section: Discussionmentioning
confidence: 99%
“…Initial studies analyzing the clinical applicability of such probes have been published, and demonstrated a very high sensitivity and specificity in distinguishing melanomas from nevi. [9][10][11][12] However, most of these studies did not examine ambiguous lesions or address clinical long-term outcomes. This study was undertaken to validate a special multicolor FISH kit in histologically ambiguous melanocytic lesions.…”
mentioning
confidence: 99%